Lipat / Muhammad Nizar Dzulkarnain Nizar Azmir - Nizar Azmir, Muhammad Nizar Dzulkarnain (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
In the realm of contemporary interior design, a distinguished wall partition can emerge as a captivating fusion of function and art. This exceptional creation seamlessly marries traditional craftsmanship with a modern aesthetic, providing a versatile and visually striking solution for spatial definition. Meticulously crafted, the partition draws inspiration from traditional Kelarai weaving, encapsulating the organic Bertam wood in its intricate patterns and textures. These designs tell a story of tradition, sustainability, and avant-garde design principles. Beyond its visual allure, this partition stands as a dynamic element that can change your space while keeping a stylish and balanced look. Invite nature into your space with a touch of art, practically showcasing the timeless charm of Malaysian craftsmanship.